Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.5194/angeo-20-547-2002
|View full text |Cite
|
Sign up to set email alerts
|

Ozone generation over the Indian Ocean during the South African biomass-burning period: case study of October 1992.

Abstract: Abstract. In this study, we present an estimation of photochemical ozone production during free tropospheric transport between the African biomass burning area and Reunion Island (Indian Ocean) by means of trajectory-chemistry model calculations. Indeed, enhanced ozone concentrations (80-100 ppbv) between 5 and 8 km height over Reunion Island are encountered during September-October when African biomass burning is active. The measurements performed during flight 10 of the TRACE-A campaign (October 6, 1992) hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…It is generally accepted that O 3 is produced in BB plumes during transport (Taupin et al, 2002;Jaffe and Wigder, 2012;Parrington et al, 2013;Arnold et al, 2015;Brocchi et al, 2018). The EnRs obtained in this study (410 -640 pptv ppbv −1 ) are in agreement with the range of EnRs obtained in tropical BB plumes older than 5 days, compiled by Jaffe and Wigder (2012), Figure 3 shows that the CAMS model reproduces correctly the O 3 concentrations at RUN outside the BB episodes but underestimates O 3 during these episodes.…”
Section: Ozone and Nosupporting
confidence: 87%
“…It is generally accepted that O 3 is produced in BB plumes during transport (Taupin et al, 2002;Jaffe and Wigder, 2012;Parrington et al, 2013;Arnold et al, 2015;Brocchi et al, 2018). The EnRs obtained in this study (410 -640 pptv ppbv −1 ) are in agreement with the range of EnRs obtained in tropical BB plumes older than 5 days, compiled by Jaffe and Wigder (2012), Figure 3 shows that the CAMS model reproduces correctly the O 3 concentrations at RUN outside the BB episodes but underestimates O 3 during these episodes.…”
Section: Ozone and Nosupporting
confidence: 87%
“…A study of the effect of tropical convection on tropospheric ozone has also been reported (Leclair de Bellevue et al,2006) and showed some differences between the two sites, Reunion and Irene. In addition, photochemical sources have been identified: biomass burning activity in Southern Africa and Madagascar during austral spring associated with long range transport of air masses are a cause of tropospheric ozone increase over Reunion Island (Baldy et al, 1996;Taupin et al, 2002). At this site, the influence of biomass burning activity has been identified between 5 and 12 km on tropospheric ozone profiles (Randriambelo et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Meteorological analysis based on trajectory statistics showed that a large part of African emissions might be advected to the Indian Ocean Piketh et al, 2002). Mechanisms responsible for regional dispersion of biomass burning emissions have been documented (Baldy et al, 1996;Taupin et al, 1999Taupin et al, , 2002. A climatology by Randriambelo et al (1999) based on ozonesonde and satellite data focuses on the relative importance of the different mechanisms.…”
Section: Regional Sourcesmentioning
confidence: 99%
“…Scattered-light solar spectra are collected along lines of sight at different elevation angles above the horizon (Hönninger et al, 2004) and analysed using DOAS least-square fitting (Platt and Stutz, 2008) to retrieve trace gas slant column densities (SCDs) by the QDOAS software package (Danckaert et al, 2017). For this analysis, NO 2 (Vandaele et al, 1998) and O 2 -O 2 (Thalman and Volkamer, 2013) were retrieved in a fitting window from 425 to 490 nm, using the further fit settings as described in Kreher et al (2020). Near-surface volume mixing ratios of NO 2 were retrieved from limb (0 • elevation angle) spectra following Dix et al (2016).…”
Section: Ground-based Remote Sensingmentioning
confidence: 99%